Estudo das propriedades ópticas e espectroscópicas de vidros cálcioboroaluminato codopados com Eu3+/Sm3+ - BRITO, Suzanny Lima de (2018)
Rare-earth (RE) codoped glasses have been strongly studied due to its optical properties. Investigations in rare-earth ions codoped glass, such as Sm3+ and Eu3+ ions, has increased significantly due to the demand by new light sources. In this work Sm3+ and Eu3+ codoped CaBAl glasses were synthesized and characterized. The samples with composition of (23-x) CaO - 50B2O3 - 15Al2O3 - 10CaF2 - 2Eu2O3 - xSm2O3, with Samarium concentration varying from 0.5 to 3 wt%, have been prepared by using melt-quenching method in air atmosphere. The glasses were prepared with a fixed concentration of Eu2O3 and different concentrations of Sm2O3 in order to understand the influence of Sm3+ and Eu3+ on the optical and spectroscopic properties of the samples. The amorphous nature of these samples was confirmed by X-ray diffraction (XRD). The increase in the volumetric density and electronic polarizability values indicated that the addition of samarium causes a modification in the structural units of the glass. The FTIR spectroscopies indicated the existence of trigonal and tetrahedral borate groups. The N4 values revealed that Sm2O3/Eu2O3 codoping favored the conversion of structural units from BO4 to BO3. From DTA analysis was observed a small change of Tg, Tx values with the increase of Sm2O3. The absorption bands were attributed to Eu3+ and Sm3+, transitions from the ground state 6H5/2 and 7F0 to the various excited states. Excitation results showed excitation peaks at 405 nm and 488 nm. The luminescence spectra, under 405 and 488 nm excitation, exhibit characteristic emission bands of Eu3+ and Sm3+. The energy transfer from the level 4G5/2 of Sm3+ to the 5D0 level of Eu3+ was verified by means of the luminescence results. With the addition of Sm3+, emission intensity of Eu3+ has been enhanced due to migration of Sm3+ excitation energy. No expressive decrease was observed in the emission intensity of Sm3+ and Eu3+ due to increase of temperature, up to 480 ºK. A decrease in lifetime of 4G5/2→6H7/2 transition with the increase of the Sm2O3 was observed, due ion-ion interactions and energy transfer from Sm3+ to Eu3+. The energy transfer efficiency (η) from Sm3+ to Eu3+ ions was estimated using the luminescence lifetimes of Sm3+ doped glasses with and without Eu3+ in 488 nm. The mechanism for energy transfer from Sm3+ to Eu3+ was studied by Dexter energy transfer equation and Reisfeld's theory on decay curves, which presented dipole-dipole nature. The above mentioned results show that the Eu3+/Sm3+ codoped CaBAl glasses have a good combination of thermal, structural and optical properties and be promising candidates to development of optical devices.